Residual gravity modelling of the Mount Mégantic intrusive complex, Québec, Canada - Seguin, Maurice K.; Frydecki, Janusz (Atlantic Geoscience, 1991)
A detailed analysis of the residual gravity anomaly of the Mount Mégantic area. Province of Quebec, Canada, has led to unconventional modelling of the intrusive masses. A new approach was developed to approximate, as closely as possible, the regional anomaly. Using the relationship between free-air anomaly and elevation it is possible to estimate the Bouguer density at each measurement station. If the variations of the Bouguer field values reflect fluctuations of a body, then the relative error of the calculated density is much smaller than that obtained using Nettleton’s method. When the density function is well defined, it is then possible to calculate the depth of the intrusive bodies at each measurement point and to determine the base of the intrusives. The masses with the greatest depth are the syenite on the southeast side of Mount M6gantic and the gabbro underneath the northern half-ring. Deep conical surfaces suggest the occurrence of conduits for the magmatic fluid at the time of intrusion. Therefore, this type of gravity modelling is useful to indicate the mode of emplacement of the intrusive bodies. Two axes, oriented west-northwest and east-southeast, characterise the deepest areas of the granite and syenite. These zones may extend downward to fault planes in the Earth’s crust beneath the intrusives. The gravity data suggest successive intrusions from syenite to gabbro to granite. These magmatic upwellings appear to have travelled through a main conduit, which is situated beneath the syenite, and also through other conduits, one of which is located under the northern gabbroic mass and another under the centre of the granitic intrusion. In this case history, we present a simplified method of gravity data interpretation, which can be effectively applied when overburden thicknesses are minimal at all density calculation points; otherwise densities will be underestimated due to the presence of significant thicknesses of low density surficial sediments. This applies to cases where bedrock geology is well known and where bedrock outcrops are observed at the surface. In addition, the size of geological bodies must be large with respect to the survey station spacing and density calculation points. This paper presents a simplified gravity modelling technique, which may be applied to regions characterized by large altitude variations and outcropping rocks. This method is directly applicable to the Monteregian Hills in southern Quebec and the eastern United States, as well as to geological bodies occurring in other parts of the world where similar conditions are encountered. RÉSUMÉ Une analyse en détail de l’anomalie gravimétrique réiduelle présente dans la région du Mont Mégantic (Province de Québec, Canada) a conduit à une modèlisation peu conventionnelle des masses intrusives. Une nouvelle approche fut développée afind’approximer le plus possible l’anomalie régionale. Il est possible d’estimer la densité de Bouguer à chaque station de mesure en utilisant la relation entre l’anomalie à l’air libre et l’élévation. Si les variations parmi les valeurs du champ de Bouguer reflètent les fluctuations d’un corps, alors l’erreur relative de la densité qui a élé calculée est beaucoup moindre que celle obtenue à l’aide de la méthode de Nettleton. Lorsque la fonction de densité est bien définie, il devient possible de calculer la profondeur des batis intrusifs à chaque poste de mesure et de déterminer leurs bases. Les masses situées à la plus grande profondeur sont la syénite sur le flanc sud-est du Mont Mégantic ainsi que le gabbro sous la moitié septentrionale du filon annulaire. Des surfaces coniques en profondeur suggérent la présence de conduits ayant acheminé le fluide magmatique au moment de l’intrusion. Ce type de modélisation gravimétrique est done utile pour déterminer le mode de mise en place des batis intrusifs. Deux axes, d’orientation ouest nord-ouest et est: sud-est, caractérisent les zones les plus profondes du granite et de la syénite. Ces zones pourraient être relayées vers le bas par des plans de faille dans la croûte terrestre en-dessous des intrusions. Les données gravimétriques suggérent une succession d’intrusions allant de la syénite au gabbro puis au granite. Ces bouffées magmatiques semblent être remontées par un conduit principal, qui se situe sous la syénite, ainsi que par d’autres conduits, dont l’un se situe sous la masse gabbro’ique septentrionale et l’autre sous le centre de l’intrusion granitique. Dans cette illustration d’un cas, nous présentons une méthode simplifiée d’interprétation des données gravimétriques, qui dorme des resultats satisfaisants la où l’épaisseur du mort-terrain est minime à tous les points de calcul de la densité; autrement, les densités seront sous-estimées par suite de la présence d’épaisseurs significatives de sédiments de surface de faible density. Ceci s’applique aux cas ou la géologie du socle est bien connue et où le socle affleure en surface. De plus, la taille des corps géologiques doit dépasser de beaucoup l’espacement des stations et des sites de calcul de la densité utilisé lors de la traverse. Cet article introduit une technique simplifiée de modèlisation gravimétrique, que l’on peut utiliser dans les régions caractérisees par de fortes variations d’altitude et où la roche affleure. Cette méthode s’applique directement aux montagnes montérégiennes du Québec méridional et des Etats-Unis orientaux, de même qu’aux corps géologiques situés ailleurs dans le monde, la où des conditions semblables sont rassemblées. [Traduit par le journal]